PENGARUH EARNINGS MANAGEMENT TERHADAP FUTURE PROFITABILITY TERKAIT DENGAN OWNERSHIP STRUCTURE, FIRM SIZE DAN CORPORATE GOVERNANCE PRACTICES - Ikhsan Yudha Asmara; Felizia Arni Rudiawarni (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2012)
This study aims to determine how the effect of earnings management on future profitability business entity engaged in the manufacturing sector listed on the Indonesia Stock Exchange, and how the effects of the ownership structure, company size, and the practice of corporate governance (proxied by the audit quality, independent board member and audit committee) regarding the impact of earnings management on the future profitability of manufacturing sector enterprises listed on the Stock Exchange. This study used a sample of manufacturing sector companies listed on the Indonesia Stock Exchange in the period 2008-2010. The samples used in this study were 262 observations. The sampling method used was probability sampling - judgment / purposive sampling. Independent variables used in this study are earnings management (proxied by the CFO, NDAC, and DAC), ownership structure (proxied by DFAM and INST), firmsize, and corporate governance practices (proxied by the AUDIT, BOD, and AUDCOM). The dependent variable in this study is the future profitability proxied by the variable